The TPP and government procurement in Malaysia - Ahamat, Haniff; Abdul Rahman, Nasarudin (Springer, 2017)
Government procurement (GP) is one of the most controversial areas in TPP, particularly for Malaysia where government procurement activities contribute significantly to the development and growth of businesses and the economy a whole. This paper seeks to investigate the impact of the TPP on Malaysian government procurement rules. While efficiency, competition, and effectiveness will be the rule of the game, the GP Chapter of the﻿ TPP can make the Malaysian legal framework regulating GP more predictable, accessible and transparent, giving value for money to consumers and taxpayers. This paper, however, will explore the challenges to procuring entities who have to comply with higher international standards when awarding contracts and to the recipients of those contracts among local companies including Bumiputera companies as they have to brace for an open GP market post-TPP. There are flexibilities offered by the GP Chapter, but there will be an issue whether those flexibilities could help balance between the positive and negative effects of the Chapter on Malaysia.